VOICES FROM THE MARGINS: PRIVACY DISCOURSE IN GITHUB README FILES - Levy-Eshkol, Keren; Ribak, Rivka (AoIR Selected Papers of Internet Research, 2023)
Most digital products use technologies that enable the collection, analysis and transfer of a considerable amount of personal information to the cloud, where it is stored and processed. Thus much of the responsibility for the users’ personal information is in the hands of the developers and the code that they author. This research adopts a materialist perspective to study developers’ discourse around the privacy solutions they embed in the code. Defining GitHub as a discursive platform, we draw on a sample of almost 60,000 README files to analyze the ways in which developers present code to other developers. We find that the files promote two approaches, privacy-by-policy and privacy-by-design. We suggest that the distinction between the two is in fact a distinction between developers who uphold privacy as a value and developers who regard it as an imposition to comply with.